Potential impact assessment for China's dry and wet areas under global warming targets. (April 2020) - Wu, Shuang; Wang, Leibin; Cai, Qixiang; Yan, Xiaodong
Abstract: Since the Industrial Revolution, greenhouse gas emissions have caused global temperatures to rise gradually. The Paris Agreement aims to limit the global mean surface temperature increase to less than 2.0 °C relative to pre-industrial levels. China's land area accounts for ∼7% of the global land (65Ñ59S) area, and the arid area of China accounts for 12.41% of the total global arid area. Therefore, the degree of aridification/humidification in China is of great significance to climate change in China and the world. This paper evaluates the regional changes of drylands and humid lands in China based on the 1.5 °C and 2.0 °C increase targets for global mean surface warming(GMSW). We find a suitable warming target for China's climate from the perspective of aridification. The results show the following: 1) If the global mean surface temperature rises by 1.5 °C and 2.0 °C above pre-industrial levels, the mean surface temperature in China will increase by 2.0 °C and 2.8 °C, respectively. 2) Under the two GMSW targets, the degree of drought in some extremely arid areas in China was projected to decrease, which means that these areas may gradually be suitable for human habitation. 3) Regardless of which global surface temperature target is maintained, the humid lands in China will bear greater risks from warming than the drylands. Under these circumstances, the 1.5 °Ctargetwill lead to better outcomes for China than the 2.0 °C target. Highlights: The degree of drought in some extremely arid areas in China has decreased under global warming targets. Humid lands in China will bear greater warming risks than the dry lands. Global warming limited within 1.5 °C target for will lead to better outcomes for China than the 2.0 °C.